1999
DOI: 10.1001/archotol.125.4.446
|View full text |Cite
|
Sign up to set email alerts
|

Otorrhea After Insertion of Silver Oxide–Impregnated Silastic Tympanostomy Tubes

Abstract: Silver oxide-impregnated tympanostomy tubes are associated with a low overall incidence of postoperative otorrhea. A significantly higher incidence of otorrhea is seen during the first postoperative week, compared with the incidence after the first week. Patients with thick middle ear effusions and age younger than 3 years have a significantly greater incidence of early otorrhea after tympanostomy tube placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…They observed a reduction of otorrhea incedences especially in long-term ventilation tube applications. With the same type of ventilation tubes, Gourin and Hubbell observed a reduction in otorrhea incidences with respect to the control set, in the period following the first week of surgery [19,20].…”
Section: Discussionmentioning
confidence: 89%
“…They observed a reduction of otorrhea incedences especially in long-term ventilation tube applications. With the same type of ventilation tubes, Gourin and Hubbell observed a reduction in otorrhea incidences with respect to the control set, in the period following the first week of surgery [19,20].…”
Section: Discussionmentioning
confidence: 89%
“…They have demonstrated that human serum albumin coating reduces early tube occlusions by preventing adherence of blood and secretion. Another tube‐coating procedure, which is silver oxide‐impregnated silastic tympanostomy tube, was used for decreasing the incidence of postoperative otorrhea 13 . However, there is no study about coating the ventilation tube with an antioxidant material in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…40 Coating is another factor that can vary with differing tympanostomy tubes. Some coatings, such as silver oxide 41 and phosphorylcholine, 42 have been suggested to reduce biofilm formation in in vitro studies but in clinical trials, this efficacy is not always apparent.…”
Section: Normal Tube Appearancementioning
confidence: 99%